Die Reformation in Schaffhausen und ihre Besonderheiten - Bryner, Erich (Zwingliana, 2012)
The Reformation in the city and countryside of Schaffhausen progressed in a surprising manner. The Benedictine monks and intellectuals of the city read Luther’s works. Through the efforts of the two Franciscans Sebastian Hofmeister and Sebastian Meyer, the Reformation became a folk’s movement. Unlike Zurich, the Schaffhausen city council rejected the Reformation at first. Only after great hesitation and due to outside pressure, the Schaffhausen city council decided in 1529 to establish the Reformation regulations and to join the Christliches Burgrecht. Although a theological leader was missing at this time, the church of Schaffhausen worked together closely with the other reformed regions in the confederation from then on; but internally, they went their own way. After extensive theological and spiritual uncertainties, the Reformed Church in Schaffhausen was secured and gained its personal profile through the efforts of Johann Conrad Ulmer.